1999
DOI: 10.1001/archinte.159.14.1607
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Size at Birth and the Development of Hypertension During Pregnancy

Abstract: Background:Whether individuals who were small at birth are at increased risk of developing cardiovascular disease (the Barker hypothesis) is a topic of great controversy. Although an increased risk has been suggested by several reports, the reports have been criticized for being based on ill-defined populations, for the large numbers of subjects who were unavailable for follow-up, and for inadequate control of socioeconomic status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
38
2
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 29 publications
(29 reference statements)
3
38
2
2
Order By: Relevance
“…This study strengthens previous findings of increased risk of pregnancy complications in women born with low birth weights. 6,[8][9][10][11][12] An inverse relation between birth weight and risk of preeclampsia and of gestational diabetes has been shown in case-control and populationbased cohort studies. 8,21,22 In a large populationbased cohort study, Zetterström and colleagues 10 found an increased risk of preeclampsia among women born small for gestational age (v. appropriate weight for gestational age).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…This study strengthens previous findings of increased risk of pregnancy complications in women born with low birth weights. 6,[8][9][10][11][12] An inverse relation between birth weight and risk of preeclampsia and of gestational diabetes has been shown in case-control and populationbased cohort studies. 8,21,22 In a large populationbased cohort study, Zetterström and colleagues 10 found an increased risk of preeclampsia among women born small for gestational age (v. appropriate weight for gestational age).…”
Section: Discussionmentioning
confidence: 98%
“…Some reports included the concept of full-term versus preterm birth and suggested an increased risk of gestational hypertension, preeclampsia or gestational diabetes among women born preterm. 6,11,12 These studies had a number of shortcomings. For example, in the studies by Klebanoff and coauthors 12 and Pouta and colleagues, 6 the participants were born between 1959 and 1966, and their average gestational age was not specified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Associations have been noted between a woman's own birth weight and her future pregnancyrelated health, including pregnancy-induced hypertension, pre-eclampsia, and gestational diabetes. [15][16][17] This, then, predisposes to adverse outcomes for her offspring, including intrauterine growth restriction and prematurity. 18 Human studies have also shown that pregnancy-induced hypertension and/or preeclampsia are associated with increased risk for chronic hypertension and subsequent kidney disease later in life.…”
mentioning
confidence: 99%